Back to my old self and life restarting: Biographies of ageing in Beck's risk society. (June 2018) - Curryer, Cassie; Gray, Mel; Byles, Julie E.
Drawing on free-text survey comments from the Australian Longitudinal Study of Women's Health (ALSWH), this article explores themes of transition and change in the lives of 150 women baby boomers (born between 1946 and 1951) in relation to Beck's theories of the risk society, reflexive modernisation and individualisation. Few studies have explicitly explored ageing through Beck's theoretical lenses. However, Beck's emphasis on interactional processes of social, individual and structural change has much to offer for sociological studies of ageing. A key premise is that of complex adaptation and change as people age, with focus on the socio-political contexts in which the post-Second World War baby boomer generation will live out their later years.